Modeling predictive factors of online health information use by urbanized Malaysian women / Syarifah Norfadzila Wan Aderus - Syarifah Norfadzila, Wan Aderus (2017)
As people become aware of health issues and realize their personal responsibility for their health, the Internet plays an important role as a source for health information. Although the number of online health information consumers has increased over the years, there are limited studies regarding online health information use by Malaysian consumers, particularly among women. People in urban areas involve in online health information seeking activity more frequently compared to people in rural areas. Therefore, the aim of this study is to investigate online health information use using urbanized Malaysian women as our study sample. Understanding the factors that contribute to online health information use in the selected scope will be beneficial for the group of people who will be affected the most. The study adopted a multi-methodological approach to information system (IS) research that integrates research model development, validation, and prototype development as a proof of concept and helps inform the research model. The study addresses three research objectives: 1) To identify factors for an enhanced research model that predict online health information use; 2) To develop an online health information use model based on the identified factors; and 3) To develop an online health information resource prototype based on the validated online health information use model. This study proposes an enhanced research model, Online Health Information Use Model (OHIUM), which consists of personal factors and online health information characteristics. Six personal factors reflect the online health information users, that is, health concern, perceived convenience, skill, health management, empowerment, and social support. Online health information characteristics consist of four factors; quality of website design, quality of content, accessibility, and credibility. Satisfaction was a mediator between online health information characteristics and online health information use. Data collection was conducted online by means of a survey questionnaire resulting in 396 completed returned responses. Using the data, OHIUM was tested and the findings provide support for the hypothesized relationships and predictive value of the model. Partial Least Squares (PLS) path modeling and descriptive analysis were used for data analysis. It was found that a total of 84% respondents reported the Internet as the main source of health information followed by doctors or advise from health professionals with 72%. The users commonly searched information for themselves (42%) and their families (40%). Factors that affect online health information use by urbanized Malaysian women are; satisfaction, empowerment, perceived convenience, health concern, and skill. Satisfaction was predicted by credibility, accessibility, and quality of content. OHIUM explained 71% of the variance in online health information use and 24% of the variance in satisfaction. It is undeniable that because online health information has great potential in helping users, it is required for the design to better suit its users’ needs. Therefore, the significant factors of validated OHIUM was incorporated into the design of Online Health Information Resource (OHIR) prototype. Data analysis of prototype evaluation show that convenience, empowerment, quality of content, credibility, and accessibility of OHIR prototype was highly perceived by participants.